ANALISIS PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP MINAT BELI ULANG PADA KONSUMEN MASKAPAI PENERBANGAN LION AIR RUTE PEKANBARU-JAKARTA - Albar, Muhammad Fachri; Jushermi, Jushermi; Rahayu, Deny Danar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to analysze Quality of Service, Price on Costumer Satisfaction and Repurchase Intention, research applied on Lion Airlines Service Consumer Pekanbaru Jakarta route. The object of this research was Lion Airlines Consumer on Pekanbaru Jakarta route. This research consists of four variables: two independent variables, one intervening variable and the dependent variable. Quality of Service (X1), Price (X2), Costumer Satisfaction (Y1) and Repurchase Intention (Y2). This research was conducted using a sample of 200 Consumer Lion Airlines who had used Lion Airlines Service Pekanbaru Jakarta route at least once. This research used purposive sampling, In terms of data analysis, this research used Path Analysis method using SPSS (Statistical Package for Social Science) version 20. Based on the hypothesis test conducted, research shows that Quality of Service has significant and positive effect toward Costumer Satisfaction, Price has significant and positive effect toward Costumer Satisfaction. Quality of Service has significant and positive effect toward Repurchase Intention, Price has significant and positive effect toward Repurchase Intention and Costumer Satisfaction has significant and positive effect toward Repurchase Intention. Quality of Service and Price Influence Repurchase Intention are moderated by Costumer Satisfaction.Keywords : Quality of Service, Price, Costumer Satisfaction, and Repurchase Intention.